Case Study of the Commercially Published ELT materials in Foundation of English Course Books 1 & 2 - Chowdhury, Md Yousuf Uddin Khaled (IIUC Studies, 2016)
Brumfit (1979) has suggested that many commercially published ELT materials are little more than masses of rubbish, skilfully marketed. He perhaps rejects most of the published materials. However, in reality, it is observed that these ELT resources are the only available alternatives in the contexts where infra-structural limitations of language classrooms and the inefficiency of the language-teachers make the goal of language learning and teaching unreachable or unattainable for many of the learners. This paper, through a case study, aims at justifying the use of commercially published ELT coursebooks that are designed and used, considering the limitations and problems of the personally produced materials by untrained teachers. Nevertheless, these materials must consider the local market rather than the global markets so that they meet the needs of the local language learners and instructors. The case study implies that it is the selection or adaptation of the right materials for the specific learners that makes them effective or ineffective. It also suggests that the personally designed or locally produced materials too may make teaching and learning difficult and impossible sometimes. IIUC Studies Vol.10 & 11 December 2014: 173-182